Metodologias, instrumentos e interfaces de organização de fotografias na web: uma análise na perspectiva do Patrimônio Cultural Rural Paulista - Silveira, Letícia Reis da (2014)
The present days are characterized by the increasingly volume of information available on different kinds of media, and proportionally by the increasingly need to think, create and evaluate methodologies and tools that deal with the processing and dissemination of relevant information to users' satisfaction. In this context, the objective of this research was to identify in what proportion some of the online systems available for organizing and retrieving photos include in their search interfaces for the user some of the major categories related to thematic processing of photographs, as surveyed and reported in the literature of Information Science. Among these systems, special attention was given to the analysis of Virtual Memory, software that has been developed within the project "Criteria and Methodologies for conducting an inventory for Rural Heritage", funded by FAPESP and coordinated by Professor Luzia Fernandes Sigoli Costa, from Federal University of São Carlos, which proposes the construction of a standard description of informational goods for the software. Methodologically, this paper is configured as an exploratory, bibliographic and documentary research, also developing actions of intervention research and using participant observation to collect data. The results indicate that relevant practices have been developed for online information systems regarding the organization of photographs and confirmation of the use of resources for social indexing as means of organization and information retrieval. Finally, it is hoped that this study can contribute to CTS field presenting what scientific literature has to offer regarding image organization, assisting in future research and suggesting ways for the construction or improvement of technological tools that give support to the imagery processing and dissemination of information to society, such as the Virtual Memory software, contributing to the process of memory and heritage of humanity.